RESEARCH ON LIQUEFIED CARBON RECOVERY IN LOW PRESSURE OIL AND GAS FIELDS - Bekjonov Rozisher Soatmurodovich (Web of Journals Publishing, 2024)
The majority of hydrocarbon gases in the world are low-pressure and flare satellite gases from oil and gas fields. Fossil gases are formed by the formation of gasses, gasses in petroleum and gases released during the process. A large volume of gas saved by mining is not used efficiently. Expensive raw materials, which are the main part of gas, are used as production capacity in industry and production.